2022
DOI: 10.3390/ph15050627
|View full text |Cite
|
Sign up to set email alerts
|

Rhinacanthin-C but Not -D Extracted from Rhinacanthus nasutus (L.) Kurz Offers Neuroprotection via ERK, CHOP, and LC3B Pathways

Abstract: Neurodegenerative diseases present an increasing problem as the world’s population ages; thus, the discovery of new drugs that prevent diseases such as Alzheimer’s, and Parkinson’s diseases are vital. In this study, Rhinacanthin-C and -D were isolated from Rhinacanthus nasustus, using ethyl acetate, followed by chromatography to isolate Rhinacanthin-C and -D. Both compounds were confirmed using NMR and ultra-performance-LCMS. Using glutamate toxicity in HT-22 cells, we measured cell viability and apoptosis, RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Interestingly, the pretreatment of cells with AHE protected against toxicity by reducing ERK phosphorylation (Figure 4A,B). Several studies demonstrated glutamate-induced toxicity through activation of ERK, which is associated with cell death in many neuronal death models, including microglial cells [37,41,57,58]. Furthermore, our investigation showed the inhibitory effect of AHE on glutamateinduced ER stress and apoptosis linked to cellular antioxidant enzymes defense in HMC3 cells.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Interestingly, the pretreatment of cells with AHE protected against toxicity by reducing ERK phosphorylation (Figure 4A,B). Several studies demonstrated glutamate-induced toxicity through activation of ERK, which is associated with cell death in many neuronal death models, including microglial cells [37,41,57,58]. Furthermore, our investigation showed the inhibitory effect of AHE on glutamateinduced ER stress and apoptosis linked to cellular antioxidant enzymes defense in HMC3 cells.…”
Section: Discussionsupporting
confidence: 53%
“…The high concentration and accumulation of glutamate are involved in ER stress in the CNS, leading to apoptotic cell death. This event can stimulate the specific ER stress proteins, including the calcium ion-mediated calpain/caspase-12 pathway or the CHOP pathway [ 35 , 36 , 37 , 38 ]. To examine the effect of AHE on ER stress-induced apoptosis caused by glutamate, we evaluated protein expression of the markers of ER stress, including calpain1, cleaved caspase-12, and CHOP, using Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation